Moderating effect of culture on the relationship between technology, motivation and quality of education in United Arab Emirates - Sameera, Iqbal (2019)
United Arab Emirtaes government enforcing policies and making a huge investment in the education sector to improve quality of education. However, still, UAE is facing quality of education problem due to certain reasons such as appropriate use of technology by learners, low motivation of students and culture differences. Therefore, the current study aims to investigate the effect of the use of technology and student motivation on education quality as well as how culture moderates these relationships; a theoretical model of the current study grounded in the united theory of acceptance and use of technology and VROOM’s expectancy theory of motivation. This study used online survey method to collect data through a questionnaire; the final sample of the study, 380 university students, was determined using simple random sampling technique. In order to empirically determine proposed relationships, this study used Partial Least Square Structural Equation Modeling (PLS-SEM) approach using SmartPLS (v.3.2.7). Moreover, the reliability and validity of the measurement model are established using the suggested criteria by previous scholars which leads to the testing of inner model and hypotheses. The findings of the structural model indicate that use of technology has a positive and significant effect on education quality, therefore, hypothesis 1 is accepted. Additionally, student motivation also has a significant and positive effect on education quality, hence, hypothesis 2 is accepted. Further, the findings of the current study revealed that culture, negatively and significantly, moderates the relationship between use of technology and education quality. Meanwhile, culture positively and significantly moderates the relationship between student motivation and education quality. Moreover, findings of the current study have several theoretical and practical implications for researchers, policymakers as well as for government to improve the quality of education in UAE.